Merdeka Belajar Policy as a Strategy to Improve Quality of Education - Imam Tabroni; Nur Aisah Jamil; Nurarita Nurarita (STAI Syaichona Moh. Cholil Bangkalan, 2022)
Currently, national education does not provide opportunities for educators and students to jointly develop students' potential and abilities. Quality education is education that has had careful planning to improve students' ability by freeing students from all forms of restraints. The quality of national education is highly dependent on the policies that support it. Nadiem Makarim created a new platform, namely Merdeka Belajar, with the latest policies aimed at changing education for the better, improving the quality of human resources in learning, and easing the burden that has been carried so far. The method used in this research is the library method. Sources of data are policies and literature related to Merdeka Belajar as a strategy to improve the quality of education. Related literature includes scientific books, journals, and articles. Analysis and interpretation of the literature through the editing process, theme classification, and meaning. The results showed that the Merdeka Belajar policy could increase students' potential, free teachers to innovate, open up school information, and increase community satisfaction with school performance.